Lightweight thermal monitoring in optical networks-on-chip via router reuse - Li, Mengquan (2020)
Optical network-on-chip (ONoC) is an emerging communication architecture for manycore systems due to low latency, high bandwidth, and low power dissipation. However, a major concern lies in its thermal susceptibility - under onchip temperature variations, functional nanophotonic devices, especially microring resonator (MR)-based devices, suffer from significant thermal-induced optical power loss, which potentially counteracts the power advantages of ONoCs and even cause functional failures. Considering the fact that temperature gradients are typically found on many-core systems, effective thermal monitoring, performing as the foundation of thermal-aware management, is critical on ONoCs. In this paper, a lightweight thermal monitoring scheme is proposed for ONoCs. We first design a temperature measurement module based on generic optical routers. It introduces trivial overheads in chip area by reusing the components in routers. A major problem with reusing optical routers is that it may potentially interfere with the normal communications in ONoCs. To address it, we then propose a time allocation strategy to schedule thermal sensing operations in the time intervals between communications. Evaluation results show that our scheme exhibits an untrimmed inaccuracy of 1.0070 K with low energy consumption of 656.38 pJ/Sa. It occupies an extremely small area of 0.0020 mm 2 , reducing the area cost by 83.74% on average compared to the state-of-the-art optical thermal sensor design.